Wady wynikające z zastosowania faktoringu - Czarecki, Jacek (Disadvantages of Factoring, 2008)
The enterprises in Poland can finance their activity and development from various sources of capital. One of them is factoring. This paper is an attempt to show negative implementing factoring in companies. The article presents both the disadvantages identified in the literature, and the faults pointed out by the surveyed factoring users. The research was carried out by the author on the basis of analysis of 43 companies. The resume has proven that the most unprofitable feature of implementing factoring in firms is the cost of this financing instrument.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1200, s. 112-120